Motivational Currents of Indonesian Postgraduate Students Studying Abroad - Rasman, Rasman (International Journal of Language Education, 2021)
Motivational currents, a relatively new concept in the field of language learning, has contributed to understanding how long-term motivational energy can be sustained among learners. Despite such critical contribution, little is known on how one of its core elements called vision, a vivid image of one’s future self, can be sustainable in such a long period. This has resulted in the difficulty for teachers to create motivational currents among their learners. This article aims at contributing to the understanding of the dynamic nature of vision in the phenomena of motivational currents. It reports on a Retrodictive Qualitative Modelling (RQM) study conducted using complex dynamic system’s frame. The data were gathered from Indonesian postgraduate students studying in a university in the United Kingdom using introspective, semi-structured interview and self-assessed motivational trajectory. They were then analyzed using Interpretative Phenomenological Analysis (IPA). The findings show that the participants experienced motivational currents although their visions or images of their future selves were slightly changing during the period. The findings will then be discussed with regards to the nature of interconnectedness between the motivational currents system and the self-system. The article is ended by outlining some pedagogical implications as well as recommendations for future research.Keywords: Motivational currents; vision; complex dynamic system.